ISLAM INKLUSIF DALAM KEHIDUPAN SOSIAL BERAGAMA DAN RELEVANSINYA DENGAN PENDIDIKAN AGAMA ISLAM PERSPEKTIF ABDURRAHMAN WAHID (GUS DUR) - Irawan, Rudy (STIT PRINGSEWU, 2024)
Abstract Abdurrahman Wahid, or who is familiarly called Gus Dur, is known as a progressive Islamic thinker who upholds inclusivity and tolerance in religious practices. This article will discuss Gus Dur's views on how Islam can be a source of inspiration for unity in social and religious diversity. By considering the values ​​of pluralism and interreligious dialogue, Gus Dur offers a new understanding of how Islamic religious education can play a key role in increasing tolerance and social harmony in a multicultural society. This research uses a qualitative approach by collecting data from Gus Dur's written works and related literature to describe contributions and opinions towards the concept of inclusive Islam and its relevance to Islamic religious education. Through this analysis, it is hoped that it can provide new insights for readers about the importance of integrating the values ​​of inclusiveness in the Islamic religious education curriculum, to achieve a society that is more open, civilized and respectful of differences. Keywords: Inclusive Islam, Religious Social Life, Islamic Religious Education